2020
DOI: 10.1111/codi.15459
|View full text |Cite
|
Sign up to set email alerts
|

Information needs for recovery after colorectal surgery: a patient focus group study

Abstract: The provision of information to patients undergoing colorectal surgery is strongly recommended in enhanced recovery guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…inaccessible language) were key barriers to effective understanding. Patients explained that good information should (i) address individualized information needs; (ii) empower patients to take an active role in their recovery; (iii) provide support through meaningful education and signposting; and (iv) recognize patients' need for information after discharge [26]. Taken together with the present findings showing that patient involvement is uncommon, it is clear that patients must be equal partners in the development of effective information resources.…”
Section: Discussionmentioning
confidence: 86%
“…inaccessible language) were key barriers to effective understanding. Patients explained that good information should (i) address individualized information needs; (ii) empower patients to take an active role in their recovery; (iii) provide support through meaningful education and signposting; and (iv) recognize patients' need for information after discharge [26]. Taken together with the present findings showing that patient involvement is uncommon, it is clear that patients must be equal partners in the development of effective information resources.…”
Section: Discussionmentioning
confidence: 86%
“…This result shows that the patients are very interested in this subject while the doctors and nurses do not care about this subject. When other studies in the literature are examined, it is seen that there is a significant difference in the opinions of nurses and patients in the information/learning requirements of the patients similar to the studies on learning requirements in discharge education (18,19) In addition, it was found in some studies that the nurses did not adequately meet the needs of the patients regarding the problems they experienced and the nurses did not have sufficient awareness in this front (6,8). This study was carried out to determine whether there were any differences between the priorities of the doctors, nurses and patient groups in the subjects of discharge training.…”
Section: Discussionmentioning
confidence: 68%
“…Previous evidence has shown that active participation is a key motivator during recovery after surgery. 30 In contrast, there are several possible challenges associated with studying and implementing nVNS in this setting. First, patient self-administration requires adequate skill, understanding and compliance, which may be difficult in the post-operative setting.…”
Section: Discussionmentioning
confidence: 99%
“…Previous evidence has shown that active participation is a key motivator during recovery after surgery. 30 …”
Section: Discussionmentioning
confidence: 99%